Diagnostic Accuracy of the Allergy Lateral Flow Assay (ALFA) Specific Allergen Test to Dermatophagoides pteronyssinus in Children Ages 8 to 18 years old Diagnosed with Allergic Rhinitis Seen at the Philippine General Hospital, Allergy Clinic - Habaña, Pia Angelica; Casis-Hao, Roxanne; Castor, Mary Anne; Recto, Marysia Stella; Sumpaico, Madeleine (Philippine Journal of Allergy, Asthma and Immunology, 2025)
Objectives: Allergic rhinitis is the most common chronic disorder in the pediatric population. The hallmark of an allergic condition is the evidence of specific IgE to an allergen. The ALFA Specific Allergen Test is a rapid in vitro assay for specific IgE. This study aims to determine the diagnostic accuracy of the ALFA Allergy System in diagnosing children aged 8 to 18 years old with allergic rhinitis. Methodology: This is a prospective study of diagnostic test accuracy performed at the Philippine General Hospital, Allergy Clinic. The skin prick test and the ALFA Specific Allergen Test to Dermatophagoides pteronyssinus were performed on 77 pediatric patients aged 8 to 18 years old with allergic rhinitis from September to February 2017. Results: The ALFA Specific Allergen Test to Dermatophagoides pteronyssinus had a sensitivity of 84.8%, specificity of 100%, positive predictive value of 100%, and negative predictive value of 81.6%. The positive likelihood ratio could not be computed since the specificity was 100%; the negative likelihood ratio was 0.15. The area under the Receiver Operating Characteristics (ROC) curve was 0.924. Conclusions: Based on the results, the ALFA Specific Allergen Test is a reliable test in determining the presence and absence of specific IgE to Dermatophagoides pteronyssinus.